2002
DOI: 10.1002/ijc.10644
|View full text |Cite
|
Sign up to set email alerts
|

PLU‐1 nuclear protein, which is upregulated in breast cancer, shows restricted expression in normal human adult tissues: A new cancer/testis antigen?

Abstract: The PLU-1 gene is expressed at the level of message in breast cancers and breast cancer cell lines and shows restricted expression in normal adult tissues with the exception of testis. The predicted protein sequence contains several domains, including the PLU domain, which is shared by other proteins involved in transcription and/or development. We have developed a polyclonal antiserum to a C-terminal fragment of the PLU-1 protein, which shows little homology to other family members. Immunohistochemic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(138 citation statements)
references
References 29 publications
7
131
0
Order By: Relevance
“…The observed deficiency seems to be quite specific for neuroectodermal derived cancers (melanomas and glioblastomas) since RBP2-H1 seems to be abundantly expressed in epithelial cancers. In accordance with our RT-PCR measurements, Barrett et al 7 reported an upregulation of PLU-1 in breast cancer. PLU-1 and RBBP2H1a represent splicing variants of RBP2-H1.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed deficiency seems to be quite specific for neuroectodermal derived cancers (melanomas and glioblastomas) since RBP2-H1 seems to be abundantly expressed in epithelial cancers. In accordance with our RT-PCR measurements, Barrett et al 7 reported an upregulation of PLU-1 in breast cancer. PLU-1 and RBBP2H1a represent splicing variants of RBP2-H1.…”
Section: Discussionsupporting
confidence: 92%
“…7,8 More detailed data on the expression of most RBPs in normal and neoplastic tissues are still lacking. While some RBPs, that is, PLU-1 and RBP-1, seem to play a role in breast cancer, 9,10 a possible impact of many other RBPs including RBP2-H1 on human cancer progression has not been investigated, yet.…”
mentioning
confidence: 99%
“…MAGE-A was seen frequently in primary ductal breast carcinomas, but not in lobular carcinomas (Otte et al, 2001). Almost 81% of the ductal carcinomas have been shown to express PLU-1 (Barrett et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] The expression of JARID1B RNA is highest in ER þ ductal carcinomas (www.oncomine.org/), being less well expressed in lobular carcinomas 8 (see Fig. 1).…”
Section: Expression Of Jarid1b In Primary Breast Tumorsmentioning
confidence: 99%
“…[7][8][9][10][11] More recently, expression of this gene in other cancers (bladder, lung, AML) has been reported and the restricted expression in normal tissues confirmed 12 suggesting a specific involvement of PLU-1/JAR-ID1B in malignancy. Moreover, the restricted expression in adult tissues makes the protein a potential therapeutic target, particularly in women.…”
mentioning
confidence: 90%